Physical activity as a health determinant in tropical built environments: a multifaceted intervention - Dahlan, Nur Dalilah; Kurmanbekova, Mainur; Mohammad Yusoff, Wardah Fatimah; Mohd Elias, Saliza (SAGE Publications, 2023)
The changing nature of technology has influenced the physical activity behaviour of working adults in tropical-built environments. Existing physical activity interventions show a lack of diversity in delivery strategies and limited local context community assimilation measures. This study aims to provide a perspective on the interventions implemented to promote physical activity in urban and rural neighbourhoods in tropical regions. Three analytical themes were synthesised from 29 screened qualitative and quantitative literature: the social context, the environmental factors and the mechanisms to promote physical activity in the built environment. The findings recognise the importance of spatial heterogeneity in physical activity promotion at midstream and downstream intervention levels in a tropical built environment. A multifaceted intervention model for positive physical activity behaviour change (MIPA) consisting of built environment variables, micro-climate conscious design, health awareness and self-efficacy factors according to the tropical built environments context is proposed.